The objective function of government-controlled banks in a financial crisis - Ogura, Yoshiaki (Journal of Banking & Finance, 2018)
We present evidence that government-controlled banks (GCBs) significantly increased their lending to small and medium-sized enterprises (SMEs) whose main bank was a large bank in the 2008–09 financial crisis. Further analyses show that the weak relationship between large banks and SMEs is a major cause for this phenomenon. The mixed Cournot oligopoly model with relationship banking, where profit-maximizing private banks and a welfare-maximizing GCB coexist, shows that this finding is consistent with the welfare maximization by a GCB rather than its own profit maximization.